A novel near-infrared fluorescent probe for visualization of intracellular hydrogen peroxide - An, Baoshuai; Pang, Shude; Zhang, Yanru; Wei, Ningning (Frontiers in Chemistry, 2022)
Hydrogen peroxide (H2O2) as a crucial reactive oxygen species (ROS) plays a crucial role in redox signaling in physiological and pathological processes of living cells. Its normal production is closely related to signal transduction of living cells. Overproduction of H2O2 in vivo has been proved to be related to many diseases. Some were developed to reveal the roles of H2O2. However, current fluorescent probes for the detection of H2O2 are restricted in their short emission wavelengths and small Stokes shifts that significantly decrease the sensitivity of detection and cellular visualization. In this work, a novel fluorescent probe BC-B was designed and synthesized with pinacol phenylboronic acid ester as a recognition group and near-infrared fluorophore BC-OH as a reporter group. BC-B probe exhibits a large Stokes shift (122 nm) and near-infrared emission (672 nm), showing an excellent selectivity and sensitivity in detection of H2O2 with the limit of 0.003 μmol/L. Confocal fluorescence imaging further demonstrates that BC-B can be used for detecting endogenous H2O2 in living cells.